2009
DOI: 10.1002/app.29959
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and anti‐TMV activity of guanidinylated chitosan hydrochloride

Abstract: In this study, guanidinylated chitosan hydrochloride (GCH) was synthesized and its structure was characterized by UV-vis and FTIR. The degree of substitution of guanidinylated chitosan was confirmed by elemental analysis. In vitro antiviral activity of guanidinium derivative on local infection and systemic infection of tobacco mosaic virus (TMV) inoculated were evaluated by semileaf method using different modes of GCH application and antiserum assay. Meanwhile, the morphological characteristic of virus treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…In agreement with our results, chitosan nanoparticles might attach to virus particles, inhibit nucleic acid replication inside infected cells, as well as boost plant immunity and antioxidant defense systems [51,58]. Electron microscope examination revealed that the TMV particles were directly affected by nanoparticles, resulting in decreased viral particles, and the majority of them twisted together and tied into a bundle, leading to virus structure rupture [55,59]. In agreement with our results, the DAS-ELISA showed the efficacy of chitosan to control CMV, PVX, and TMV infections [51,58,60].…”
Section: Antiviral Activity Of Chitosan/dextran Nanoparticles (Cdnps)...supporting
confidence: 88%
“…In agreement with our results, chitosan nanoparticles might attach to virus particles, inhibit nucleic acid replication inside infected cells, as well as boost plant immunity and antioxidant defense systems [51,58]. Electron microscope examination revealed that the TMV particles were directly affected by nanoparticles, resulting in decreased viral particles, and the majority of them twisted together and tied into a bundle, leading to virus structure rupture [55,59]. In agreement with our results, the DAS-ELISA showed the efficacy of chitosan to control CMV, PVX, and TMV infections [51,58,60].…”
Section: Antiviral Activity Of Chitosan/dextran Nanoparticles (Cdnps)...supporting
confidence: 88%
“…CS existing as a disassociated form in solution with an extending conformation, which ensures sufficient contact with bacteria, resulting in better antibacterial activity. In an attempt to increase the antibacterial activity of CS over a wide pH range, the feasibility of chitosan/guanidine polymers was investigated by many researchers [ 53 , 54 ]. These studies suggest that the attachment of the guanidine group onto CS can introduce positive charges on the polymer backbone, which results in better aqueous solubility with enhanced antimicrobial activity at neutral pH.…”
Section: Introductionmentioning
confidence: 99%
“…2 ). Moreover, GCH showed direct killing activity by damaging the viral structure which was observed as flocculation in electron microscopic photographs [ 40 ]. Along similar lines, a study conducted by Noiket et al, treated a Thai variety of tomato plant Sridathip 3 which grows mostly in the Thailand peninsula and infected by Tomato yellow leaf curl virus diseases (TYLCV) with chitosan.…”
Section: Chitosan and Its Derivatives Combating Plant Virusesmentioning
confidence: 99%